Ketahanan Masyarakat terhadap Ancaman Krisis Energi Listrik di Kabupaten Lampung Selatan, Provinsi Lampung - Helmia Adita Fitra; Asirin Asirin (Department of Urban and Regional Planning, Diponegoro University, 2018)
Lampung Province is facing energy crisis problems. Due to the deficit of electricity supplies which is up to 200 Megawatt (MW), power shutdowns have emerged in many areas of Lampung Province. As one of the districts in South Lampung Regency, Jati Agung is located adjacent to Bandar Lampung City. Jati Agung has access to Trans-Sumatera Highway which is indicated by the entrance and exit gate of the highway. Moreover, there is a new educational activity, Institut Teknologi Sumatera, and a governmental activity called Kota Baru. As a potential fast-growing district in Lampung Province, Jati Agung needs a community resilience strategy to cope with the current threat of electricity crisis in Jati Agung, South Lampung. This research aims to map the community resilience dimension to the threat of electricity crisis in Jati Agung, South Lampung based on the community perception. In this study, the community is represented by household units which are located in the study area. This study is expected to examine how resilient of each dimension about the electricity crisis in the study area. The community resilience dimension has four categories, i.e. 1) Health and Wellbeing, 2) Economy and Society, 3) Infrastructure and Environment, and 4) Leadership and Strategy. This research conducts a descriptive statistics analysis by using a Likert scale to assess community resilience for each driving factor in each dimension. The result shows that “Leadership and Strategy” dimension has the lowest score and classified as a “poor resilience” dimension.